Inequality and aggregate savings in the neoclassical growth model - Reto Foellmi (University of Bern, Department of Economics, 2010)
Within the context of the neoclassical growth model I investigate the implications of (initial) endowment inequality when the rich have a higher marginal savings rate than the poor. More unequal societies grow faster in the transition process, and therefore exhibit a higher speed of convergence. Furthermore, there is divergence in consumption and lifetime wealth if the rich exhibit a higher intertemporal elasticity of substitution. Unlike the Solow-Stiglitz model, the steady state is always unique although the consumption function is concave.
Keywords: O40; D30; O10; 330; marginal propensity to consume; income distribution; growth; concave consumption function; Gesamtwirtschaftliche Konsumfunktion; Soziale Ungleichheit; Einkommensverteilung; Solow-Modell; Wachstumstheorie; Neoklassik; Theorie